2023
DOI: 10.2174/1573404819666221031154700
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Haptonomy Intervention on Fear of Childbirth and Maternal- Fetal Attachment Among Primigravid Women

Abstract: Background: Fear of childbirth (FOC) is considered as one of the factors influencing the increase of elective cesarean section. The appropriate solution to reduce the FOC has not yet been identified. Objective: The present study aimed to evaluate the effect of haptonomy intervention on FOC and maternal-fetal attachment (MFA) among primigravid women‎. Methods: This quasi-experimental study was conducted on 68 primigravid women with a gestational age of 24-28 weeks who referred to health centers in Tabriz, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, Klabbers et al [ 30 ] reported a significant reduction in the FOC mean score of pregnant following 8-session of haptonomy. In the study of Dorosti [ 33 ] on primigravida women with high and severe FOC, a significant reduction in the FOC was observed in the intervention group compared to the control group following five sessions of haptonomy intervention. To the best of our knowledge, the results of all studies investigated the effect of haptonomy on FOC are consistent and this has been acknowleged as an effective technique in reducing FOC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Klabbers et al [ 30 ] reported a significant reduction in the FOC mean score of pregnant following 8-session of haptonomy. In the study of Dorosti [ 33 ] on primigravida women with high and severe FOC, a significant reduction in the FOC was observed in the intervention group compared to the control group following five sessions of haptonomy intervention. To the best of our knowledge, the results of all studies investigated the effect of haptonomy on FOC are consistent and this has been acknowleged as an effective technique in reducing FOC.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on the FOC variable in the study of Dorosti et al [ 33 ] using G Power software. Considering m 1 = 93, m 2 = 79.05, with the assumption of 15% reduction, SD1 = SD2 = 16.93, and two-sided hypothesis, and Power = 90%, sample size was obtained 30 in each group and regarding 10% attrition, the final sample size was 33 in each group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations